PENINGKATAN PRODUKTIVITAS JAGUNG DI INDONESIA - Agus Hudoyo; Indah Nurmayasari (Lampung University, 2019)
The objective of this study was to know the impact of the efforts on increasing of the corn yield in Indonesia. The data used in this study are the FAO’s data. They were analyzed by using the econometric model. It is the multiple regression model which its dependent variable is the corn yield and its independent variables are six dummy variables for differentiating seven periods of the intensification programs. The data are time series, i.e. from 1961 to 2017. The result revealed that the intensification programs had been statistically significant in increasing the corn productivity. At the beginning of the green revolution (1961-1967), the average of its productivity was 0.97 ton/ha and in the period 2015-2017 (Upsus), the average of its productivity was 5.23 ton/ha. In this period, the average increase in productivity was 0.32 ton/ha/year which was the highest compared with the periods of the other intensification program.Keywords: corn yield; increase; intensification